TRANSLANGUAGING IN EFL CLASSROOMS: TEACHERS’ BELIEFS AND PURPOSES IN KAZAKHSTAN - Yakshi, Sumeie (Nazarbayev University Graduate School of Education, 2022)
According to previous research, monolingual assumptions remain popular among Kazakhstani educators, which contradicts translanguaging pedagogy. Although the majority of teachers strongly oppose the use of translanguaging in the classroom they still use it for various purposes. However, previous studies have not considered these purposes using theories on translanguaging, nor connected directly the relationship between beliefs and purposes. Therefore, this study aimed to explore EFL teachers' beliefs on translanguaging and the purposes of using it in the classroom. In order to achieve this goal, the two research questions were posed: 1) What are the teachers' beliefs about using translanguaging in the classroom? 2) What purposes do EFL teachers have for using translanguaging? The study used Macaro's (2001) theoretical framework for beliefs and Garcia et al. (2017) theory for translanguaging purposes to answer the research questions. The study collected data through qualitative semi-structured interviews and classroom observations for triangulation. Overall, four EFL teachers from Shymkent BIL school participated in interviews, and eight classroom observations were conducted with these teachers. The study revealed that three participants had the maximal position and occasionally resorted to learners' L1, while one participant showed a virtual position and preferred English-only instruction. Although teachers held different positions, they all used translanguaging for four specific purposes of Garcia et al. (2017). Firstly, translanguaging was used to support students’ engagement and comprehension of the complex content and text. Secondly, with the help of translanguaging teachers provided opportunities to develop linguistic practices for academic contexts. Thirdly, teachers made spaces for students’ multilingualism and ways of knowing. Fourthly, teachers supported students’ socio-emotional development and well-being. Nevertheless, all participants experienced guilt and regret for their translanguaging practices even though they acknowledged its benefits. Besides, despite their translanguaging practices, teachers used monolingual assessment, and the reasons for this practice could be another direction for future research.
Keywords: Translanguaging; Translanguaging in EFL classrooms; Translanguaging beliefs; Translanguaging purposes; Teachers' translanguaging beliefs; Teachers' translanguaging purposes